High-throughput spheroid screens using volume, resazurin reduction and acid phosphatase activity - Ivanov, Delyan Pavlov; Grabowska, Anna M.; Garnett, Martin C. (Humana Press (Springer), 2017)
Mainstream adoption of physiologically-relevant three-dimensional models has been slow in the last 50 years due to long, manual protocols with poor reproducibility, high price and closed commercial platforms. This chapter describes high-throughput, low-cost, open methods for spheroid viability assessment which use readily-available reagents and open-source software to analyse spheroid volume, metabolism and enzymatic activity. We provide two ImageJ macros for automated spheroid size determination - for both single images and for images in stacks. We also share an Excel template spreadsheet allowing users to rapidly process spheroid size data, analyse plate uniformity (such as edge effects and systematic seeding errors), detect outliers and calculate dose-response. The methods would be useful to researchers in preclinical and translational research planning to move away from simplistic monolayer studies and explore 3D spheroid screens for drug safety and efficacy without substantial investment in money or time.